Preparation method of composite electrode
By forming TNAs on the Ti sheet of the biosensor and depositing silver films and Prussian blue films on their surfaces, the problems of easy interference at high potentials in the prior art are solved, and the Prussian blue stability are achieved, thereby achieving efficient, stable and selective detection of composite electrodes.
Patent Information
- Application Number
- CN202411725772.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When existing biosensors detect H2O2 at high potential, they are easily disturbed by electroactive substances, and the binding force of Prussian blue modified electrodes is weak and the stability is poor.
Using the composite electrode preparation method, a titanium dioxide nanotube array (TNAs) was formed by pretreating the Ti sheet, and then a silver film and a Prussian blue film were deposited on its surface to form a TNAs/Ag/PB composite electrode.
It improves electrocatalytic activity, mechanical strength and stability, reduces interference from electroactive substances, and enhances the selectivity and accuracy of H2O2 detection.
Smart Images

Figure CN119780189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biosensor electrodes, and in particular to a method for preparing a composite electrode. Background Art
[0002] A biosensor is an instrument that is sensitive to biological substances and converts their concentration into electrical signals for detection. The detection mode of oxidase biosensors is usually the oxidation reaction product H catalyzed by the enzyme substrate and oxygen. 2 O 2 Electrochemical detection. This method can detect lower substrate concentrations and is therefore widely used in the preparation of biosensors. 2 O 2 Electrochemical oxidation detection is usually performed by applying a voltage of 0.6 V (vs. Ag / AgCl) to a platinum electrode. However, there are many electroactive substances in biological samples, such as ascorbic acid, bilirubin, uric acid, etc., which can also be oxidized at such a high potential, which will interfere with the H 2 O 2 Therefore, how to selectively and efficiently catalyze H 2 O 2 It has become a hot topic in current research.
[0003] Titanium dioxide nanotube arrays (TNAs) are a kind of nanostructure composed of single-layer or multi-layer titanium dioxide nanotubes. At present, the main method for preparing TNAs is anodization. The TNAs prepared by this method grow directly on the Ti sheet substrate and are arranged in an orderly array. The nanotubes are directly connected to the Ti sheet, and the combination is firm, the distribution is uniform, and it is not easy to be washed away. It has a high active specific surface area and good chemical thermal stability, as well as very strong mechanical strength. At the same time, the preparation technology is simple and the cost is low. These advantages make TNAs a promising functional material, which has been widely used in the fields of hydrogen sensitive elements, solar cells and biosensors.
[0004] Prussian Blue (PB), also known as ferric ferrocyanide, is one of the known classic coordination polymers. It has long been used as a light-stable material in the industrial production of coatings, baking enamels, printing ink colorants and detergent additives. Prussian Blue is also known as "artificial peroxidase". Its thin film modified electrode is sensitive to H 2 O 2 The catalytic performance was good, with PB as H 2 O 2 The reduced medium can effectively solve the detection of H 2 O 2At present, the methods of PB modification on electrodes are mainly electrochemical deposition, continuous ion adsorption, mechanical attachment to electrodes and layer deposition. However, there are still many problems to be solved, such as the weak binding force between PB and electrodes. After a few cycles of cyclic voltammetry in the solution, it is easy to fall off from the electrode surface, resulting in poor stability. Summary of the invention
[0005] In order to overcome the shortcomings and deficiencies of the prior art, the present invention aims to provide a method for preparing a composite electrode, wherein the prepared composite electrode has excellent electrocatalytic activity, mechanical strength and stability, and is simple to prepare and has low cost.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a composite electrode comprises the following steps: (1) The Ti sheet was ultrasonically cleaned in acetone, ethanol, and deionized water for 15 min, then placed in a mixed acid solution for chemical polishing for 30 s with vigorous stirring, then taken out and cleaned with deionized water, and dried at room temperature to obtain a pretreated Ti sheet; (2) A two-electrode system is formed with a constant voltage DC power supply as the power source, a pretreated Ti sheet as the anode, and a Pt wire as the cathode. The pretreated Ti sheet is corroded in HF ethanol solution, NaF and HF buffer solution, and HF aqueous solution at a voltage of 20-30 V for 30-45 min with continuous stirring, then cleaned with deionized water, placed in a muffle furnace and calcined for 1 h, and TNAs are obtained after cooling; (3) Using a saturated calomel electrode as the reference electrode, a three-electrode system is formed with the two-electrode system. Under constant voltage, the TNAs are immersed in a silver nitrate solution and the current density is maintained at 1-2 mA / cm 2 4min, a silver film was deposited on the surface of TNAs, and the TNAs / Ag composite electrode was obtained after washing with deionized water and drying naturally; (4) Soak the TNAs / Ag composite electrode in K 3 Fe(CN) 6 In a mixed solution of and KCl, cyclic voltammetry was scanned for 150 cycles with a scanning voltage of -0.2-0.6V, and a PB film was deposited on the TNAs / Ag composite electrode. After washing with deionized water and drying naturally, a TNAs / Ag / PB composite electrode was obtained.
[0007] Preferably, the Ti sheet has a size of 1 mm×15 mm×0.1 mm.
[0008] Preferably, the purity of the Ti flakes is 99.9%.
[0009] Preferably, the mixed acid solution is a mixed solution of HF, concentrated nitric acid and deionized water in a volume ratio of 1:4:5.
[0010] Preferably, the concentration of the HF ethanol solution is 0.2%-0.3%, and the concentration of the HF aqueous solution is 0.2%-0.3%.
[0011] Preferably, the pH value of the NaF and HF buffer is 5-5.2.
[0012] Preferably, the temperature of the muffle furnace is 500°C.
[0013] Preferably, the concentration of the silver nitrate solution is 20-30 mmol / L.
[0014] Preferably, the K 3 Fe(CN) 6 K in a mixed solution of KCl 3 Fe(CN) 6 The concentration is 1-2mmol / L, and the KCl concentration is 0.1-0.2mol / L.
[0015] Preferably, the K 3 Fe(CN) 6 The pH value of the mixed solution of MgCl and KCl is 1.5-1.7.
[0016] Beneficial effects of the present invention: The TNAs in the composite electrode prepared by the present invention are uniformly and neatly arranged nanotube arrays and are directly grown on the Ti sheet substrate, are firmly bonded, evenly distributed, not easily washed away, and have strong mechanical strength. Using TNAs as carriers to load Ag thin films thereon can not only improve the conductivity of TNAs and improve the electrocatalytic activity of the composite electrode, but also can be closely bonded with the PB thin film through electrostatic force, thereby solving the problem that PB is easily detached from the electrode surface and improving the stability of the composite electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is the cyclic voltammetry curve of Example 1 before and after 300 cycles; Figure 2 This is the cyclic voltammetry curve of Comparative Example 2 before and after 300 cycles. DETAILED DESCRIPTION
[0018] The concept and technical effects of the present invention will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present invention. Embodiment 1:
[0019] The method for preparing the composite electrode described in this embodiment comprises the following steps: (1) Ti sheet pretreatment: A Ti sheet (1 mm × 15 mm × 0.1 mm) with a purity of 99.9% was ultrasonically cleaned in acetone, ethanol, and deionized water for 15 min, then placed in a mixed solution of HF, concentrated nitric acid, and deionized water in a volume ratio of 1:4:5 for chemical polishing for 30 s and stirred vigorously. Then, the Ti sheet was taken out and cleaned with deionized water and dried at room temperature to obtain a pretreated Ti sheet. (2) Preparation of TNAs: A two-electrode system was formed using a constant voltage DC power supply as the power source, a pretreated Ti sheet as the anode, and a Pt wire as the cathode. The pretreated Ti sheet was corroded in a 0.2% HF ethanol solution, a buffer solution of NaF and HF with a pH value of 5, and a 0.2% HF aqueous solution at a voltage of 20 V for 30 min with continuous stirring. The sheet was then cleaned with deionized water and calcined in a muffle furnace at 500 °C for 1 h. TNAs were obtained after cooling. (3) Deposition of Ag thin film: Using a saturated calomel electrode as the reference electrode, a three-electrode system is formed with the two-electrode system. Under constant voltage, the TNAs are immersed in a 20-30 mmol / L silver nitrate solution and the current density is maintained at 1 mA / cm 2 4min, a silver film was deposited on the surface of TNAs, and the TNAs / Ag composite electrode was obtained after washing with deionized water and drying naturally; (4) Deposition of PB film: The TNAs / Ag composite electrode was immersed in 1 mmol / L K 3 Fe(CN) 6 The PB film was deposited on the TNAs / Ag composite electrode in a mixed solution of 0.1 mol / L KCl, and the electrode was scanned by cyclic voltammetry for 150 cycles at a scanning voltage of -0.2-0.6 V. The TNAs / Ag / PB composite electrode was washed with deionized water and dried naturally to obtain the TNAs / Ag / PB composite electrode. Embodiment 2:
[0020] The method for preparing the composite electrode described in this embodiment comprises the following steps: (1) Ti sheet pretreatment: A Ti sheet (1 mm × 15 mm × 0.1 mm) with a purity of 99.9% was ultrasonically cleaned in acetone, ethanol, and deionized water for 15 min, then placed in a mixed solution of HF, concentrated nitric acid, and deionized water in a volume ratio of 1:4:5 for chemical polishing for 30 s and stirred vigorously. Then, the Ti sheet was taken out and cleaned with deionized water and dried at room temperature to obtain a pretreated Ti sheet. (2) Preparation of TNAs: A two-electrode system was formed using a constant voltage DC power supply as the power source, a pretreated Ti sheet as the anode, and a Pt wire as the cathode. The pretreated Ti sheet was corroded in 0.25% HF ethanol solution, a buffer solution of NaF and HF with a pH value of 5.1, and a 0.25% HF aqueous solution at a voltage of 25 V for 35 min with continuous stirring. The sheet was then cleaned with deionized water and calcined in a muffle furnace at 500 °C for 1 h. TNAs were obtained after cooling. (3) Deposition of Ag thin film: Using a saturated calomel electrode as the reference electrode, a three-electrode system was formed with the two-electrode system. Under constant voltage, the TNAs were immersed in a 25 mmol / L silver nitrate solution and the current density was maintained at 1.5 mA / cm 2 4min, a silver film was deposited on the surface of TNAs, and the TNAs / Ag composite electrode was obtained after washing with deionized water and drying naturally; (4) Deposition of PB film: The TNAs / Ag composite electrode was immersed in 1.5 mmol / L K 3 Fe(CN) 6 In a mixed solution of 0.15 mol / L KCl, cyclic voltammetry was performed for 150 cycles with a scanning voltage of -0.2-0.6 V. A PB film was deposited on the TNAs / Ag composite electrode. After washing with deionized water and drying naturally, a TNAs / Ag / PB composite electrode was obtained. …… Embodiment 3:
[0021] The method for preparing the composite electrode described in this embodiment comprises the following steps: (1) Ti sheet pretreatment: A Ti sheet (1 mm × 15 mm × 0.1 mm) with a purity of 99.9% was ultrasonically cleaned in acetone, ethanol, and deionized water for 15 min, then placed in a mixed solution of HF, concentrated nitric acid, and deionized water in a volume ratio of 1:4:5 for chemical polishing for 30 s and stirred vigorously. Then, the Ti sheet was taken out and cleaned with deionized water and dried at room temperature to obtain a pretreated Ti sheet. (2) Preparation of TNAs: A two-electrode system was formed using a constant voltage DC power supply as the power source, a pretreated Ti sheet as the anode, and a Pt wire as the cathode. The pretreated Ti sheet was corroded in a 0.3% HF ethanol solution, a buffer solution of NaF and HF with a pH value of 5.2, and a 0.3% HF aqueous solution at a voltage of 30 V for 45 min with continuous stirring. The sheet was then cleaned with deionized water and calcined in a muffle furnace at 500 °C for 1 h. TNAs were obtained after cooling. (3) Deposition of Ag thin film: Using a saturated calomel electrode as the reference electrode, a three-electrode system was formed with the two-electrode system. Under constant voltage, the TNAs were immersed in a 30 mmol / L silver nitrate solution and the current density was maintained at 2 mA / cm 24min, a silver film was deposited on the surface of TNAs, and the TNAs / Ag composite electrode was obtained after washing with deionized water and drying naturally; (4) Deposition of PB film: The TNAs / Ag composite electrode was immersed in 2 mmol / L K 3 Fe(CN) 6 The PB film was deposited on the TNAs / Ag composite electrode in a mixed solution of 0.2 mol / L KCl and 150 cycles of cyclic voltammetry with a scanning voltage of -0.2-0.6 V. The TNAs / Ag / PB composite electrode was washed with deionized water and dried naturally to obtain a TNAs / Ag / PB composite electrode.
[0022] Comparative Example 1: The difference between this comparative example and Example 1 is that TNAs are not prepared and Ti sheets are used instead of TNAs for loading. The other raw materials and steps are the same as those in Example 1.
[0023] Comparative Example 2: The difference between this comparative example and Example 1 is that the deposition of the Ag thin film is not performed, and the other raw materials and steps are the same as those in Example 1.
[0024] Composite electrode performance test: Stability test: The electrodes prepared in Example 1 and Comparative Example 2 were placed in a 0.1 mol / L PBS solution (pH 6.0, containing 0.1 mol / L KCl), with a voltage range of -0.05-0.5 V and a scan rate of 50 mV / s for 300 consecutive scans.
[0025] Depend on Figure 1 and Figure 2 It can be seen that the electrode peak current of Comparative Example 2 is smaller than that of Example 1, and the electrocatalytic activity is poor; and after 300 cycles, the peak current of the electrode of Comparative Example 2 is smaller than that of Example 1, and the electrocatalytic activity is poor. 2 O 2 The electrochemical response degree of the embodiment 1 is greatly reduced, and the peak current drops significantly, showing poor stability. However, the curve of Example 1 is roughly unchanged after 300 cycles, and has excellent stability. This is because the Ag film loaded on the TNAs in Example 1 can not only improve the conductivity of the TNAs and improve the electrocatalytic activity of the composite electrode, but also can be closely combined with the PB film through electrostatic force, solving the problem that PB is easy to fall off from the electrode surface, and improving the stability of the composite electrode.
[0026] Mechanical strength test: The composite electrodes prepared in Examples 1-3 and Comparative Examples 1-2 were placed in a compression testing machine, a certain pressure was applied, and the compression deformation and compression force of the composite electrodes were measured, thereby calculating the mechanical strength of the composite electrodes.
[0027] Table 1: Composite electrode strength test Strength / MPa Example 1 2.24 Example 2 2.37 Example 3 2.31 Comparative Example 1 1.06 Comparative Example 2 2.07 It can be seen from the above table that the mechanical strength of Comparative Example 1 is worse than that of Example 1. This is because Comparative Example 1 did not prepare TNAs and used Ti sheets instead of TNAs for loading, while the TNAs prepared in Example 1 were uniformly and neatly arranged nanotube arrays and grew directly on the Ti sheet substrate, which were firmly bonded, evenly distributed, not easily washed away, and had strong mechanical strength.
[0028] The above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a composite electrode, characterized in that: The steps include: (1) Pretreatment of Ti sheet: The Ti sheet was ultrasonically cleaned in acetone, ethanol and deionized water for 15 min, then placed in a mixed acid solution for chemical polishing for 30 s and stirred vigorously, then taken out and cleaned with deionized water, and dried at room temperature to obtain a pretreated Ti sheet; (2) Preparation of TNAs: A two-electrode system was formed using a constant voltage DC power supply as the power source, a pretreated Ti sheet as the anode, and a Pt wire as the cathode. The pretreated Ti sheet was corroded in HF ethanol solution, NaF and HF buffer solution, and HF aqueous solution at a voltage of 20-30 V for 30-45 min with continuous stirring. The sheet was then cleaned with deionized water and calcined in a muffle furnace for 1 h. TNAs were obtained after cooling. (3) Deposition of Ag thin film: Using a saturated calomel electrode as the reference electrode, a three-electrode system is formed with the two-electrode system. Under constant voltage, TNAs are immersed in a silver nitrate solution and the current density is maintained at 1-2 mA / cm 2 4min, a silver film was deposited on the surface of TNAs, and the TNAs / Ag composite electrode was obtained after washing with deionized water and drying naturally; (4) Deposition of PB film: The TNAs / Ag composite electrode was immersed in a mixed solution of K3Fe(CN)6 and KCl. The cyclic voltammetry was performed for 150 cycles with a scanning voltage of -0.2-0.6 V to deposit a PB film on the TNAs / Ag composite electrode. The electrode was then washed with deionized water and dried naturally to obtain a TNAs / Ag / PB composite electrode.
2. The method for preparing a composite electrode according to claim 1, characterized in that: The Ti sheet has a size of 1 mm×15 mm×0.1 mm.
3. A method for preparing a composite electrode according to any one of claims 1 to 2, characterized in that: The purity of the Ti sheet is 99.9%.
4. The method for preparing a composite electrode according to claim 1, characterized in that: The mixed acid solution is a mixed solution of HF, concentrated nitric acid and deionized water in a volume ratio of 1:4:
5.
5. The method for preparing a composite electrode according to claim 1, characterized in that: The concentration of the HF ethanol solution is 0.2%-0.3%, and the concentration of the HF aqueous solution is 0.2%-0.3%.
6. The method for preparing a composite electrode according to claim 1, characterized in that: The pH value of the NaF and HF buffer is 5-5.
2.
7. The method for preparing a composite electrode according to claim 1, characterized in that: The temperature of the muffle furnace is 500°C.
8. The method for preparing a composite electrode according to claim 1, characterized in that: The concentration of the silver nitrate solution is 20-30 mmol / L.
9. The method for preparing a composite electrode according to claim 1, characterized in that: In the mixed solution of K3Fe(CN)6 and KCl, the concentration of K3Fe(CN)6 is 1-2 mmol / L, and the concentration of KCl is 0.1-0.2 mol / L.
10. A method for preparing a composite electrode according to any one of claims 1 or 9, characterized in that: The pH value of the mixed solution of K3Fe(CN)6 and KCl is 1.5-1.7.
Citation Information
Patent Citations
A TiO2 nanotube array photoanode and its preparation method
CN102280269A
Preparation method for silver bismuthate-silver-titanium dioxide nanotube array and application thereof
CN109030594A
Upright graphene electron mediator electrode material and preparation method thereof
CN114775008A